High-performance green electronic substrate employing flexible and transparent cellulose films. (15th October 2021) - Sun, Yanling; Chen, Dan; Li, Yang; Sun, Shuang; Zheng, Jiaqi; Cui, Jingqiang; Wang, Guosheng; Zheng, Li; Wang, Yunming; Zhou, Huamin
Abstract: Today's widely used and rapidly updated electronic substrates are composed of petroleum-based polymers, but the resulting electronic waste (such as Dioxin, oxole, PCBs, etc.) will cause massive harm to the environment and human body. Therefore, we report an effective approach for fabricating recyclable and high-performance cellulose films as green electronic substrates by calendering. The crosslinking between CH and CHCH in cellulose modified by maleic anhydride led to the in-situ formation of a chemical crosslinking network, and hydrogen bonds acted as a sacrificial physical crosslinking network. The dual crosslinked cellulose film exhibits high strength (120.56 MPa), improved elongation (increased by 263%), and outstanding thermal stability (thermal decomposition temperature is 311 °C). Further, the film has been successfully used as a substrate for biomass sensor and realized apparent responses to changes. The scientific strategy paves the way for the large-scale fabrication of high-performance cellulose films and simultaneously promotes green electronic substrates' industrialization. Graphical abstract: A green electronic substrate is realized based on high-performance flexible cellulose films with dual cross-linking networks. Unlabelled Image Highlights: A strategy combining chemical and physical crosslinking networks was reported. The film had high tensile strength (120.56 MPa) and an improved elongation of 263%. Thermal stability was superior to RF and CCF due to its more stable structure. The properties of the film offered its potential as an electronic substrate.